IMPLEMENTASI ASAS KETERBUKAAN DALAM PENYUSUNAN PERATURAN DAERAH - Dani, Akhmad (Solusi, 2021)
The principle of openness is the principle that determines that every activity and the final result of one example in making a regional regulation must be accountable to the people as the highest sovereignty. One of the main features in the formation of regional regulations must be transparency. One of the important elements in the context of realizing good governance is the existence of good regional regulation management. The government is required to be open and guarantee access to control holders to various information regarding the public policy process, budget allocations for policy implementation, as well as monitoring and evaluation of policy implementation. There are 2 factors that influence the implementation of the principle of openness of the Regional People's Representative Council (DPRD) in the preparation of Regional Regulations, there are 2 supporting factors, namely the availability of adequate facilities and infrastructure, the willingness of experts and procurement personnel on duty, and the presence of DPRD members (on time). Inhibiting factors are the lack of understanding or uneven understanding of DPRD Members on the preparation of Regional Regulations, ineffective communication patterns, late submissions of Budget Work Plans from the City Government, some DPRD members seem to prioritize party interests rather than those of the people, and DPRD still consider the results of the stipulation of Regional Regulations. (document) is confidential.